Tetrachoric correlation as a measure of default correlation - Noyan, Fatma; Simsek, Gulhayat Golbasi (ELSEVIER SCIENCE BV, 2012)
Default correlation is a crucial in risk management. The aim of this paper is to introduce a new method for measuring default correlation. In this paper we recall tetrachoric correlation coefficient which is a measure of association between two continuous variables that have each been measured on a dichotomous scale. We presented the applicability of tetrachoric correlation as a default risk correlation measure. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Arasli
Keywords: Default correlation; tetrachoric correlation; Business & Economics